Isokinetic Extension Strength Is Associated With Single-Leg Vertical Jump Height - Fischer, Felix (Orthop J Sports Med, 2017)
BACKGROUND: Isokinetic strength testing is an important tool in the evaluation of the physical capacities of athletes as well as for decision making regarding return to sports after anterior cruciate ligament (ACL) reconstruction in both athletes and the lay population. However, isokinetic testing is time consuming and requires special testing equipment. HYPOTHESIS: A single-jump test, regardless of leg dominance, may provide information regarding knee extension strength through the use of correlation analysis of jump height and peak torque of isokinetic muscle strength. STUDY DESIGN: Cross-sectional study; Level of evidence, 3. METHODS: A total of 169 patients who underwent ACL reconstruction were included in this study. Isokinetic testing was performed on the injured and noninjured legs. Additionally, a single-leg countermovement jump was performed to assess jump height using a jump accelerometer sensor. Extension strength values were used to assess the association between isokinetic muscle strength and jump height. RESULTS: The sample consisted of 60 female (mean age, 20.8 ± 8.3 years; mean weight, 61.7 ± 6.5 kg; mean height, 167.7 ± 5.3 cm) and 109 male (mean age, 23.2 ± 7.7 years; mean weight, 74.6 ± 10.2 kg; mean height, 179.9 ± 6.9 cm) patients. Bivariate correlation analysis showed an association (r = 0.56, P < .001) between jump height and isokinetic extension strength on the noninvolved side as well as an association (r = 0.52, P < .001) for the involved side. Regression analysis showed that in addition to jump height (beta = 0.49, P < .001), sex (beta = –0.17, P = .008) and body mass index (beta = 0.37, P < .001) affected isokinetic strength. The final model explained 51.1% of the variance in isokinetic muscle strength, with jump height having the strongest impact (beta = 0.49, P < .001) and explaining 31.5% of the variance. CONCLUSION: Initial analysis showed a strong association between isokinetic strength and jump height. The study population encompassed various backgrounds, skill levels, and activity profiles, which might have affected the outcome. Even after controlling for age and sex, isokinetic strength was still moderately associated with jump height. Therefore, the jump technique and type of sport should be considered in future research.